Blood‐brain barrier dysfunction in canine epileptic seizures detected by dynamic contrast‐enhanced magnetic resonance imaging. (29th April 2019) - Hanael, Erez; Veksler, Ronel; Friedman, Alon; Bar‐Klein, Guy; Senatorov, Vladimir V.; Kaufer, Daniela; Konstantin, Lilach; Elkin, Maria; Chai, Orit; Peery, Dana; Shamir, Merav H.
Abstract: Objective: Dogs with spontaneous or acquired epilepsy exhibit resemblance in etiology and disease course to humans, potentially offering a translational model of the human disease. Blood‐brain barrier dysfunction (BBBD) has been shown to partake in epileptogenesis in experimental models of epilepsy. To test the hypothesis that BBBD can be detected in dogs with naturally occurring seizures, we developed a linear dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) analysis algorithm that was validated in clinical cases of seizing dogs and experimental epileptic rats. Methods: Forty‐six dogs with naturally occurring seizures of different etiologies and 12 induced epilepsy rats were imaged using DCE‐MRI. Six healthy dogs and 12 naive rats served as control. DCE‐MRI was analyzed by linear‐dynamic method. BBBD scores were calculated in whole brain and in specific brain regions. Immunofluorescence analysis for transforming growth factor beta (TGF‐β) pathway proteins was performed on the piriform cortex of epileptic dogs. Results: We found BBBD in 37% of dogs with seizures. A significantly higher cerebrospinal fluid to serum albumin ratio was found in dogs with BBBD relative to dogs with intact blood‐brain barrier (BBB). A significant difference was found between epileptic and control rats when BBBD scores were calculated for the piriform cortex at 48 hours and 1 month after status epilepticus. Mean BBBD score of the piriform lobe in idiopathic epilepsy (IE) dogs was significantly higher compared to control. Immunohistochemistry results suggested active TGF‐β signaling and neuroinflammation in the piriform cortex of dogs with IE, showing increased levels of serum albumin colocalized with glial acidic fibrillary protein and pSMAD2 in an area where BBBD had been detected by linear DCE‐MRI. Significance: Detection of BBBD in dogs with naturally occurring epilepsy provides the ground for future studies for evaluation of novel treatment targeting the disrupted BBB. The involvement of the piriform lobe seen using our linear DCE‐MRI protocol and algorithm emphasizes the possibility of using dogs as a translational model for the human disease.